Islamic Studies in Sumatera: Prospects and Challenges - Zuhri Zuhri (AJIS: Academic Journal of Islamic Studies, 2016)
Discussing about Islamic studies in the territorial context has long been mentioned by observers in contemporary Islamic studies after the collapse of orientalist’s paradigm, however, in the territorial context of Indonesia, a regional Islamic studies has not been mentioned at all. Whereas, materially, both in the context of humanity nor religion, it is very urgent for being researched and developed in Indonesia, both from science, research, or institutional side. This article tries to start the efforts above by targeting the Islamic studies of Sumatra. The growth history and also interaction’s dynamics of religion and socials, the struggle between religion and power as reflected in the results of studies about classical Islam of Sumatera, both in the colonialism and post-colonialism era indicated a shift in issues knots. In the context of Islamic studies, that fact is a prospective land and also a challenge for further investigation. Because in each shift, the existence of religion and religious are always in disadvantaged position. Therefore, it is needed to revitalize Islamic studies on Sumatra that was driven by the higher religious education in order to maintain the existence and contribution for meeting the various dynamics and relations issues, also the conflicts of interest among religion, humanity, capitalism, environmental and power which have been more complex lately, particularly in Sumatera. Keywords: Islam, Islamic Studies, Sumatera